IMPROVING ECONOMIC DIRECTIONS FOR DEVELOPING SERVICES IN RURAL AREAS OF THE REGION ON THE BASIS OF GREEN ECONOMY AND ECOLOGICAL SUSTAINABILITY - Taylakova, Dilafruz Baymamatovna (THE INNOVATION ECONOMY, 2026)
This article scientifically studies the issues of improving the economic directions of the development of the service sector in rural areas of the Republic of Uzbekistan based on the principles of a green economy and environmental sustainability. In 2024, the share of the service sector in the GDP of Uzbekistan reached 47.4 percent, and the growth rate of the sector was 7.7 percent. However, the service market in rural areas remains significantly underdeveloped compared to urban areas. The goal of increasing the volume of service provision by 3 times is set within the framework of the "Uzbekistan - 2030" strategy (No. PF-158, September 12, 2023). In achieving this goal, the rapid development of the green services sector (ecotourism, organic agro-industrial services, energy-saving utilities, digital financial services) in rural areas plays an important role.